Physicochemical modifications of sugarcane and cassava agro-industrial wastes for applications as biosorbents. (September 2019) - de Oliveira, André Vinícius Bueno; Rizzato, Tânia Mara; Barros, Beatriz Cervejeira Bolanho; Favaro, Silvia Luciana; Caetano, Wilker; Hioka, Noboru; Batistela, Vagner Roberto
Abstract: The destination of agro-industrial waste becomes an increasing problem especially for agricultural countries. In this work, physicochemical modifications were performed in agro-industrial residues of sugarcane and cassava, aiming to describe their potential application as biosorbents. All raw materials were treated with NaOH 0.10 mol L −1 and the ashes were produced by carbonization and calcining at 600 °C for 6 h. The biosorbents were characterized in terms of chemical composition, pHzpc, ATR-FTIR, XRD, MEV and textural analysis. The adsorption studies were performed at pH 3.0, 7.0 and 11.0 for 2 h at 25.0 °C, according to Box-Behnken's design. The response surfaces showed the best performance rate of adsorption in basic media due to the negative superficial charges that interact with cationic dye MB. Results demonstrated that sugarcane and cassava residues can be used as biosorbents without the need of transformations into ashes, which leads to a more sustainable destination. Graphical abstract: Unlabelled Image Highlights: Biosorbents were characterized regarding their chemical composition and physicochemical parameters. The adsorption promoted by the sugarcane's ashes was similar to that of the raw material. Cassava's ashes present low adsorption capacity due to the loss of organic groups. The action of sugarcane biosorbents was more efficient at pH 11.0. The Temkin model best describes the adsorption behavior of SCB and CAW.